Melting of cryocrystals at high pressures. Computer simulation - Yakub, E.S. (Физика низких температур, 2015)
Simple molecular models were applied to predict melting temperature of highly compressed classical molecular
crystals of hydrogen and nitrogen in a wide range of pressures and temperatures using conventional molecular
dynamics simulation. It was shown that models which comprise noncentral interaction can reproduce turnover
of the melting line observed at megabar pressures. We discuss the relation of this effect to the parameters of
chemical bonding